Temporal Association of Certain Neuropsychiatric Disorders Following Vaccination of Children and Adolescents: A Pilot Case–Control Study - Leslie, Douglas L.; Kobre, Robert A.; Richmand, Brian J.; Aktan Guloksuz, Selin; Leckman, James F. (Frontiers in Psychiatry, 2017)
Abstract Background: Although the association of the MMR vaccine with autism spectrum disorder has been convincingly disproven, the onset of certain brain-related autoimmune and inflammatory disorders has been found to be temporally associated with the antecedent administration of various vaccines. This study examines whether antecedent vaccinations are associated with increased incidence of obsessive-compulsive disorder (OCD), anorexia nervosa (AN), anxiety disorder, chronic tic disorder, ADHD, major depressive disorder, and bipolar disorder in a national sample of privately insured children. Methods: Using claims data, we compared the prior year's occurrence of vaccinations in children and adolescents ages 6 to 15 years with the above neuropsychiatric disorders that were newly diagnosed between January 2002 and December 2007, as well as two control conditions, broken bones and open wounds. Subjects were matched with controls according to age, gender, geographical area and seasonality. Conditional logistic regression models were used to determine the association of prior vaccinations with each condition. Results: Subjects with newly diagnosed AN were more likely than controls to have had any vaccination in the previous 3 months (hazard ratio [HR] 1.80, 95% confidence interval [95%CI] 1.21-2.68). Influenza vaccinations during the prior 3, 6-, and 12- months were also associated with incident diagnoses of AN, OCD, and an anxiety disorder. Several other associations were also significant with HRs greater than 1.40 (Hepatitis A with OCD and AN; Hepatitis B with AN; and meningitis with AN and chronic tic disorder). Conclusions: This pilot epidemiologic analysis implies that the onset of some neuropsychiatric disorders may be temporally related to prior vaccinations in a subset of individuals. These findings warrant further investigation, but do not prove a causal role of antecedent infections or vaccinations in the pathoetiology of these conditions. Given the modest magnitude of these findings in contrast to the clear public health benefits of the timely administration of vaccines in preventing mortality and morbidity in childhood infectious diseases, we encourage families to maintain vaccination schedules according to CDC guidelines.